Bacteriophage application on red meats and poultry: Effects on Salmonella population in final ground products. (May 2017) - Yeh, Y.; Purushothaman, P.; Gupta, N.; Ragnone, M.; Verma, S.C.; de Mello, A.S.
Abstract: This research was conducted to study the effects of bacteriophage application during tumbling on Salmonella populations in ground meat and poultry. Red meat trim and poultry were inoculated with a Salmonella cocktail to result in a contamination level of 7 log CFU/g in ground products. A commercial preparation containing bacteriophages S16 and Felix-O1a (FO1a) was applied during tumbling at 10 7 and 10 8  PFU/ml. Samples were held at 4 °C for 6 h and 18 h (red meat) and 30 min and 6 h (poultry). Overall, bacteriophage application on trim reduced 1 and 0.8 log CFU/g of Salmonell a in ground beef and ground pork, respectively. For ground chicken and ground turkey, Salmonella was reduced by 1.1 and 0.9 log CFU/g, respectively. This study shows that bacteriophage application during tumbling of red meat trim and poultry can provide additional Salmonella contro l in ground products. Highlights: Bacteriophage application reduced Salmonella in ground meat and poultry. Bacteriophage can be applied on meats by using existent equipment and adopting current methodologies. Bacteriophage application on trim at 10 8  PFU/ml reduced approximately 1 log CFU/g of Salmonella in ground products. Bacteriophages were able to reduce Salmonella in meats under processing temperatures.